Our Unruly Signs, and How We Cope with Them - Floyd Merrell (Opción, 2005)
This paper suggests some premises that should inhere in any viableaccount of what C. S. Peirce called a logic of vagueness, a logic in thebroadest possible sense. These premises revolve around complementaryinterrelations between overdetermination and underdetermination,vagueness and generality, and inconsistency and incompleteness, thecombination of them bearing a threat to the classical principles of Identity,Non-Contradiction, and Excluded-Middle. However, fortunatelyfor us, it is through our detouring around these classical principles thatwe are able to cope with our everyday apparently unruly, illogical signs.